Frontispiece: Stable Organic Radicals Participation in Charge Transfer: A New Strategy toward Molecular Functional Materials. Issue 15 (14th March 2023) - Xu, Jieqiong; Li, Shengkai; Yang, Yanxia; Chen, Zhuo
Abstract : Stable organic radicals can serve as ideal building blocks for the construction of molecular functional materials due to their unique open‐shell structures. In this Concept, both recent experimental progress and design strategies of stable organic radicals participating in charge transfer as open‐shell donors, acceptors, and dimers to construct functional materials are discussed.